Deforestation process in the municipality of Cherán, Michoacán, México (2006-2012) - España-Boquera, María Luisa; Champo-Jiménez, Omar (Instituto de Ecología, A.C., 2016)
The devastation of ecosystems in recent years is increasing the inequality and social conflict, and in particular, the marginalization of indigenous people, who in many cases are the rightful owners of the forestland. In this research we analyse the case of the Purepecha town of Cheran, Michoacan, community that in 2011, staged an armed uprising as protest for the illegal logging of their forests, in the face of the indifference of the authorities. The annual loss of forest cover between 2006 and 2012 was estimated by analyzing high resolution satellite images Spot (10 m), using a criterion based on the NDVI and the spectral signature. Soil / vegetation maps were obtained and validated for each year of the period studied; the comparison of annual maps allowed to generate the map of annual deforestation. In total, 9000 ha were deforested, equivalent to 71% of the vegetation area existing in 2006. Most deforestation occurred between 2010 and 2011 (2815 ha) and corresponds to the forest nearest the urban core area; many clearcuts were also burned. These results measure the problem of deforestation in Cheran and help understand the community’s reaction to the destruction of their forest.